The New Testament in color: a multiethnic Bible commentary - McCaulley, Esau; Ok, Janette H.; Padilla, Osvaldo; Peeler, Amy L. B. (IVP Academic, 2024)
"In this one-volume commentary, a multiethnic team of scholars holding orthodox Christian beliefs brings exegetical expertise coupled with a unique interpretive lens to illuminate the ways social location and biblical interpretation work together. These diverse scholars offer a better vantage point for both the academy and the church"--